Supporting Factors in Searching for Childbirth Assistance for the Anak Dalam Tribe (SAD) Community in Bungo Regency, Indonesia - Ridwan, M; Sari, Puspita; Ningsih, Vinna Rahayu (Universitas Aisyah Pringsewu, 2021)
Maternal mortality in Jambi Province has increased from 46 cases in 2018 to 59 cases in 2019. Childbirth out in health facilities is a specific problem in this province, especially in districts with Anak Dalam Tribe (SAD) communities, one of which is a district of Bungo. SAD residents rely more on delivery assistance and general medical treatment of their citizens to someone passed down from generation to generation called Kepaco'an, a term that residents more accept than traditional midwives. This study aims to analyse supporting factors to search for childbirth assistance in this community. The results showed that there had been a division of roles between Kepaco'an and health workers (midwives), but the midwife’s roles between Kepaco’an and health workers (midwives), but the midwife’s role was trivial. The main supporting factor is trust, where kepaco'an is passed down from generation to generation, while midwives are considered very young and inexperienced. Childbirth procedure with “jampe-jampe” makes to mother and family become calm is the next supporting factor. In addition, the cost of childbirth is cheaper and the distance to health facilities is quite far also factor in childbirth to Kepaco'an. Increasing trust in health workers is essential and cannot be ignored through a partnership pattern by assigning more experienced health workers. Continuous mentoring of SAD families with the involvement of tumenggung and Kepaco'an and shaping internal changes through midwifery education for SAD residents is an effective step in increasing childbirth with health workers, which has an impact on reducing maternal mortality in this district. Kematian ibu di Provinsi Jambi mengalami peningkatan dari 46 kasus di tahun 2018 ke 59 kasus di tahun 2019. Persalinan yang tidak dilaksanakan di fasilitas kesehatan menjadi permasalahan spesifik di provinsi ini, terutama di kabupaten yang memiliki komunitas Suku Anak Dalam (SAD), salah satunya Kabupaten Bungo. Warga SAD lebih memercayakan pertolongan persalinan dan pengobatan umum warganya kepada seseorang yang terpilih secara turun temurun yang dipanggil Kepaco’an, sebuah istilah yang lebih diterima oleh warga daripada dukun bayi. Penelitian ini bertujuan menggali lebih dalam faktor pendukung pencarian pertolongan persalinan pada komunitas ini. Hasil penelitian menunjukkan telah terdapat pembagian peran antara kepaco’an dan tenaga kesehatan (bidan), akan tetapi peran bidan sangat kecil. Faktor pendukung utama adalah kepercayaan, dimana kepaco’an terpilih secara turun temurun, sedangkan bidan dianggap masih sangat muda dan belum berpengalaman. Prosedur persalinan dengan jampe-jampe sehingga ibu dan keluarga menjadi tenang adalah faktor pendukung selanjutnya. Selain itu, biaya persalinan yang lebih murah dan jarak tempuh ke fasilitas kesehatan yang cukup jauh juga menjadi faktor persalinan dilakukan kepada kepaco’an. Meningkatkan kepercayaan kepada tenaga kesehatan menjadi hal penting yang tidak dapat diabaikan melalui pola kemitraan, tentunya dengan menugaskan tenaga kesehatan yang lebih berpengalaman. Pendampingan keluarga SAD secara kontinue dengan keterlibatan tumenggung dan kepaco’an serta membentuk perubahan internal melalui pemberian pendidikan kebidanan bagi warga SAD merupakan langkah efektif dalam peningkatan persalinan ke petugas kesehatan yang tentunya berdampak pada penurunan angka kematian ibu di kabupaten ini.